Biological Soil Crust From Mesic Forests Promote a Specific Bacteria Community - Glaser, Karin; Albrecht, Martin; Baumann, Karen; Overmann, Jörg; Sikorski, Johannes (Frontiers in Microbiology, 2022)
Biological soil crusts (biocrusts) harbor a diverse community of various microorganisms with microalgae as primary producers and bacteria living in close association. In mesic regions, biocrusts emerge rapidly on disturbed surface soil in forest, typically after clear cut or wind fall. It is unclear whether the bacterial community in biocrusts is similar to the community of the surrounding soil or if biocrust formation promotes a specific bacterial community. Also, many of the interactions between bacteria and algae in biocrusts are largely unknown. Through high-throughput-sequencing analysis of the bacterial community composition, correlated drivers and the interpretation of biological interactions in a biocrust of a forest ecosystem, we show that the bacterial community in the biocrust represents a subset of the community of the neighboring soil. Bacterial families connected with degradation of large carbon molecules, like cellulose and chitin, and the bacterivore Bdellovibrio were more abundant in the biocrust compared to bulk soil. This points to a closer interaction and nutrient recycling in the biocrust compared to bulk soil. Furthermore, the bacterial richness was positively correlated with the content of mucilage producing algae. The bacteria likely profit from the mucilage sheaths of the algae, either as carbon source or protectant from grazing or desiccation. Comparative sequence analyses revealed pronounced differences between the biocrusts bacterial microbiome. It seems that the bacterial community of the biocrust is recruited from the local soil, resulting in specific bacterial communities in different geographic regions.